Variasi Bahasa Berdasarkan Kelas Sosial Tokoh dalam Novel Bumi Manusia Karya Pramoedya Ananta Toer - Sa’adah Fuji Astutik; Magfirotul Hamdiah (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
This study aims to describe language variation based on the social class of the characters in Bumi Manusia by Pramoedya Ananta Toer through a sociolinguistic approach. This research employed a descriptive qualitative method using reading, observation, and note-taking techniques. The data consisted of dialogues among characters containing language variations that reflect social stratification. The data were analyzed using the theory of language variation and sociolect proposed by Chaer and Agustina. The findings reveal three dominant language varieties: Dutch, Javanese Krama, and Bazaar Malay. Dutch is predominantly used by European characters and educated indigenous people as a symbol of social status, education, and colonial power. Javanese Krama functions as a marker of politeness, respect, and hierarchical social relationships within Javanese culture. Meanwhile, Bazaar Malay is commonly used by lower-class indigenous characters as a simple and egalitarian means of daily communication. These language varieties demonstrate that language functions not only as a communication tool but also as a marker of social identity, social status, power relations, and character interactions within the colonial society portrayed in the novel. Therefore, language variation in Bumi Manusia represents social stratification and serves as an essential element in depicting colonial social reality.